Solving the diagnostic dilemma in bone infections: metagenomic next generation sequencing enhances pathogen identification accuracy - Xiao, Jiheng; Pu, Congli; Zhou, Xianglong; Zhang, Xiaokang; Zhang, Shanshan; Yang, Puxin; Zhang, Yingze; Xiong, Liming (Frontiers in Medicine, 2026)
ObjectiveMetagenomic Next Generation Sequencing (mNGS) offers a rapid, unbiased, and culture-independent approach to pathogen identification by analyzing all nucleic acids present in clinical samples. Despite its growing use, the diagnostic utility of mNGS in bone infections remains inadequately characterized. This study aimed to assess the diagnostic accuracy of mNGS compared to conventional microbial cultures and to explore its associations with clinical severity and patient outcomes.MethodsWe retrospectively enrolled 135 adult patients treated for suspected bone infections between October 2023 to January 2025 at Union Hospital, Tongji Medical College. Among these, 101 patients were classified as the infection group (IG) based on clinical and laboratory criteria, encompassing osteomyelitis, post-traumatic limb infections, and diabetic foot infections. mNGS results were compared to traditional cultures in terms of sensitivity, specificity, predictive values, and discordant cases. The IG was further stratified into mNGS-positive (n = 95) and mNGS-negative (n = 6) subgroups. Clinical parameters—including leukocyte differentials, C-reactive protein (CRP), procalcitonin (PCT), albumin, length of hospital stay, and mortality—were analyzed in relation to mNGS findings.ResultsAmong all patients, 74.81% were confirmed to have infections. mNGS demonstrated a markedly higher sensitivity than culture (94.06% vs. 47.52%, p = 0.000) while maintaining comparable specificity (85.29% vs. 76.47%, p = 0.549). Age showed a potential trend in influencing mNGS positivity (p = 0.092). Although not statistically significant, mNGS-positive patients tended to have longer hospitalizations (p = 0.098), suggesting possible associations with infection complexity or pathogen load.ConclusionmNGS substantially enhances the diagnostic yield for bone infections, particularly in polymicrobial, low-abundance, or culture-negative scenarios. mNGS-negative patients had significantly shorter hospital stays and a lower rehospitalization rate. Its rapid and comprehensive pathogen detection may enable more timely and targeted antimicrobial therapy, potentially improving patient outcomes and reducing healthcare burden. These findings support the integration of mNGS as a valuable adjunct to conventional diagnostic workflows in orthopedic infectious diseases.